'Brewing the Truth': Craft Beer, Class and Place in Contemporary London. (October 2019) - Wallace, Andrew
Neo-artisanal production is a growing milieu of contemporary urban cultural economy. This article positions one area of this neo-artisanship – 'craft' beer brewing – as pivotal to this urban milieu. It draws on 25 qualitative interviews with craft brewers and brewery owners in London and critically unpacks how the 'crafting' of beer involves entanglements with and alterations of social and material space. The article offers accounts of London craft brewery owners' creative and commercial dispositions and the spatial and aesthetic patterns emerging out of London's craft beer boom and troubles the weaving of craft brewing by policymakers and real estate developers into restructuring and place-making agendas. The article suggests that the 'authentication' of livelihoods, tastes and places through the tactile promise of 'craft' cannot be decoupled from patterns of socio-spatial stratification and growing precarity and casts doubt upon any 'creative' urban economy shifting in this direction.